Prevalence of the coinfection of the hepatitis B and Delta viruses among graduates at an university in Belém, Pará, Brazil (Research, Society and Development, 2021)
Introduction: The human Hepadnavirus are a kind of viruses responsible for the severe ailment of the liver, an essential organ for the perfect operation of the human body; this process happens as the viral hepatitis, which in Brazil,  still reaches na elevated number of individuals. Objective: This research intends to demonstrate the prevalence and epidemiologic characteristics of the Hepatitis B and Delta viruses in graduates at na University in Belém, Pará, Brazil. Materials and methods: This is a transversal study in which the academicians of the University Of Amazon, from the Alcindo Cacela campus whose attended the inclusion and exclusion criteria, willingly volunteered to participate in the research. The participants were applied a questionnaire to gather lifestyle information and immunochromatographic assay that, in the case of reactive result for hepatitis B, was to be followed by a blood sampling for posterior use in the ELISA assay in search of the HDVAg antigen. Results: 100 participants were included in this study, of which 44 (44%) of the participants were female, and 56 (56%) male. There was detected no cases of hepatitis Delta in the population involved. Conclusion: The prevalence of active (acute) cases of hepatitis B and/or Delta in the academic community is null, however, over 10% participants stated  to have already had contact with hepatitis.